THE LOOSING SOUL IN GHAZAL 119 POEM BY JALALUDDIN RUMI (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2015)
This study is a brief explanation of the description of the loosing soul in Rumi’s Ghazal 119 poem and the explanation of the representation of Rumi’s unconsciousness. The analysis used the method of documentation, reduction, and data display. The roles of the researcher are data collector, classifier, analyzer, and interpreter. The result of the study proved that the loosing soul had been discovered trough bad characters and behavior of the narrator’s companion which appeared in the poem. Furthermore, Rumi’s unconsciousness had been discovered as the way of thinking which was influenced by the soul. Then, the way of thinking would also affect someone’s characters and choice of life. The soul has the biggest influence because it is the center of human being which controls the whole body. Thus, soul must be filled with sweetness, tenderness, and spiritualism.